In-Vitro Comparative Study of the Effect of Four Finishing and Polishing Tools on Surface Roughness of a Microhybrid Resin Composite - S Nemati Anarakiu; H Kazemi; Z GHafari; Z Naser; T Bitaraf (Islamic Azad University, 2019)
Background and Aim: The complications of unwanted surface roughness of composite restorations are highly common due to the increasing use of this restorative material. Therefore, the present study was designed to compare the effect of four finishing and polishing (F&P) tools on surface roughness of microhybrid resin composites. Materials and Methods: This experimental study was performed on 42 samples of CLEARFIL™ AP-X ​​microhybrid composite, which were divided into four groups of different F&P methods and one control group as follows: control (n=2), Flexi-D discs (n=10), Flexi-D + diamond polishing paste (n=10), Intensive twisted rubber polisher (n=10), and Rubber Polisher Teco (n=10). The samples were examined by profilometry. Surface roughness (Ra) of each specimen was measured at three points, and the mean value was considered as surface roughness. The results were analyzed by analysis of variance (ANOVA) and post hoc statistical tests. Results: The surface roughness of composite discs in an ascending order was as follows: control (0.048±0.014 µm), Flexi-D disc (0.179±0.132 µm), Intensive twisted rubber polisher (0.233±0.105 µm), Flexi-D disc with diamond polishing paste (0.232±0.141 µm), and Rubber Polisher Teco (0.251±0.087 µm; P=0.001). The difference between the two groups of Flexi-D disc with diamond polishing paste and Rubber Polisher Teco was not statistically significant (P=0.742). The level of surface roughness in Flexi-D samples was significantly lower than that of the other samples (P<0.05). Conclusion: It seems that the Flexi-D disc is the best F&P tool for microhybrid resin composites.